2022
DOI: 10.7150/thno.72826
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-based genome-wide screening for deubiquitinase subfamily identifies USP1 regulating MAST1-driven cisplatin-resistance in cancer cells

Abstract: Background: Cisplatin is one of the frontline anticancer agents. However, development of cisplatin-resistance limits the therapeutic efficacy of cisplatin-based treatment. The expression of microtubule-associated serine/ threonine kinase 1 (MAST1) is a primary factor driving cisplatin-resistance in cancers by rewiring the MEK pathway. However, the mechanisms responsible for MAST1 regulation in conferring drug resistance is unknown. Methods: We implemented a CRISPR/Cas9-based, genome-wide, dual screening system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The direct binding between MAST1 and hsp90 increases the stabilization of MAST1, as the ubiquitination of lysines 317 and 545 of MAST1 by CHIP is inhibited [45]. A recent study revealed that the stability of MAST1 is also enhanced by the deubiquitinase USP1 in cisplatin-resistant cancer cells [44]. Together, these findings suggest that Hsp90, MAST1 and USP1 may be excellent targets for cisplatin-resistant cancer cells, as their inhibition will enhance cisplatin sensitivity and result in increased cell death.…”
Section: Association Of Mast Kinase Mutations In Cancermentioning
confidence: 96%
“…The direct binding between MAST1 and hsp90 increases the stabilization of MAST1, as the ubiquitination of lysines 317 and 545 of MAST1 by CHIP is inhibited [45]. A recent study revealed that the stability of MAST1 is also enhanced by the deubiquitinase USP1 in cisplatin-resistant cancer cells [44]. Together, these findings suggest that Hsp90, MAST1 and USP1 may be excellent targets for cisplatin-resistant cancer cells, as their inhibition will enhance cisplatin sensitivity and result in increased cell death.…”
Section: Association Of Mast Kinase Mutations In Cancermentioning
confidence: 96%
“…93 Acting as an USP1 inhibitor, pimozide, a diphenyl-butylpiperidine compound, effectively overcomes cancer cell resistance to cisplatin and demonstrates potent inhibition of lung tumor growth both in vitro and in vivo. 94 Similarly, other USP1 inhibitors, including ML323, C527, SJB2-043, SJB3-019A, and KSQ-4279, have shown the ability to induce cell cycle arrest and cell death in a spectrum of malignancies, encompassing esophageal squamous cell carcinoma, leukemia, and multiple myeloma, both in vitro and in vivo settings [95][96][97][98] (Figure 7A). Hence, targeting USP1 presents a promising opportunity for anti-cancer therapy.…”
Section: Usp1 Inhibitormentioning
confidence: 97%
“…Pimozide, a medication clinically used for Tourette syndrome, inhibits the DUB activity of USP1, resulting in increased levels of PCNA and FANCD2 mono‐ubiquitination 93 . Acting as an USP1 inhibitor, pimozide, a diphenyl‐butylpiperidine compound, effectively overcomes cancer cell resistance to cisplatin and demonstrates potent inhibition of lung tumor growth both in vitro and in vivo 94 . Similarly, other USP1 inhibitors, including ML323, C527, SJB2‐043, SJB3‐019A, and KSQ‐4279, have shown the ability to induce cell cycle arrest and cell death in a spectrum of malignancies, encompassing esophageal squamous cell carcinoma, leukemia, and multiple myeloma, both in vitro and in vivo settings 95–98 (Figure 7A).…”
Section: Therapeutic Potential Of Dub Inhibitorsmentioning
confidence: 99%
“…[28][29][30][31] Given its promising potential in gene therapy, CRISPR/Cas9 has expanded rapidly in biomedical research of cancer treatment. 24,[32][33][34] Different CRISPR/ Cas9-mediated cancer therapy approaches, such as altering chemo-tolerance genes, changing metabolically relevant genes and tumor stem cell associated genes, as well as cancer immunotherapy, are well-established in diverse cancer types. 32,[35][36][37][38] Although the discovery of CRISPR/Cas9 paved the way for simple, effective, and multiplex manipulation of genes, the off-target impacts, difficulties in targeting specific cells in vivo, and the successful transfer into the nuclei still remain the main obstacles keeping it from realizing its maximum capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Given its promising potential in gene therapy, CRISPR/Cas9 has expanded rapidly in biomedical research of cancer treatment 24,32–34 . Different CRISPR/Cas9‐mediated cancer therapy approaches, such as altering chemo‐tolerance genes, changing metabolically relevant genes and tumor stem cell associated genes, as well as cancer immunotherapy, are well‐established in diverse cancer types 32,35–38 .…”
Section: Introductionmentioning
confidence: 99%